IN SITU STUDY of GOLD FUNCTIONALIZATION SURFACE for PROTEIN IMMOBILIZATION - dos Santos, Adriano [UNESP]; Ribeiro, Willian Campos [UNESP]; Bueno, Paulo Roberto [UNESP] (Ecletica Quimica, 2014)
The SAM approach for biological material immobilization is currently used in biosensors devices, for analytical and protein affinity studies. This paper focuses on the study of real time SAM formation consisted of mixed SAM of 11-mercaptoundecanoic acid (MUA) and 6-mercapto-1-hexanol, in a molar ratio of 1:3, on gold surface, by QCM-D and cyclic voltammetry techniques. It was confirmed that the SAM is a packed film, with high degree of surface coverage. As an example of protein adsorption on the SAM, it was studied, by QCM-D technique, the adsorption process of gelatin. The results demonstrate that the adsorption and coverage processes occur in a single step, resulting in the formation of a protein monolayer. This is an interesting result since it partially assures the use of Langmuir isotherm model to study protein affinity and analytical responses.
ESTUDO in SITU DA FUNCIONALIZAÇÃO DE SUPERFÍCIE DE OURO PARA IMOBILIZAÇÃO DE PROTEÍNA
Keywords: Protein adsorption; QCM-D; SAM